Preparation of liposomal amiodarone and investigation of its cardiomyocyte-targeting ability in cardiac radiofrequency ablation rat model - Zhuge Y (Dove Medical Press, 2016)
Ying Zhuge,1,* Zhi-Feng Zheng,1,* Mu-Qing Xie,2 Lin Li,2 Fang Wang,1 Feng Gao2,3 1Department of Cardiology, Shanghai First People’s Hospital of Nanjing Medical University, 2Department of Pharmaceutics, School of Pharmacy, 3Shanghai Key Laboratory of Functional Materials Chemistry, East China University of Science and Technology, Shanghai, People’s Republic of China*These authors contributed equally to this workAbstract: The objective of this study was to develop an amiodarone hydrochloride (ADHC)-loaded liposome (ADHC-L) formulation and investigate its potential for cardiomyocyte targeting after cardiac radiofrequency ablation (CA) in vivo. The ADHC-L was prepared by thin-film method combined with ultrasonication and extrusion. The preparation process was optimized by Box–Behnken design with encapsulation efficiency as the main evaluation index. The optimum formulation was quantitatively obtained with a diameter of 99.9±0.4 nm, a zeta potential of 35.1±10.9 mV, and an encapsulation efficiency of 99.5%±13.3%. Transmission electron microscopy showed that the liposomes were spherical particles with integrated bilayers and well dispersed with high colloidal stability. Pharmacokinetic studies were investigated in rats after intravenous administration, which revealed that compared with free ADHC treatment, ADHC-L treatment showed a 5.1-fold increase in the area under the plasma drug concentration–time curve over a period of 24 hours (AUC0–24 h) and an 8.5-fold increase in mean residence time, suggesting that ADHC-L could facilitate drug release in a more stable and sustained manner while increasing the circulation time of ADHC, especially in the blood. Biodistribution studies of ADHC-L demonstrated that ADHC concentration in the heart was 4.1 times higher after ADHC-L treatment in CA rat model compared with ADHC-L sham-operated treatment at 20 minutes postinjection. Fluorescence imaging studies further proved that the heart-targeting ability of ADHC-L was mainly due to the CA in rats. These results strongly support that ADHC-L could be exploited as a potential heart-targeting drug delivery system with enhanced bioavailability and reduced side effects for arrhythmia treatment after CA.Keywords: liposomes, cardiomyocyte targeting, amiodarone hydrochloride, cardiac radiofrequency ablation